Analisis Pengaruh Kelembagaan terhadap Kinerja Bongkar Batubara di Pelabuhan - Frilia Esti Anggraeni; Indriyani Indriyani (SAINTARA, 2022)
The less than optimal role of institutions in terms of unsystematic unloading services is one of the causes of the decline in unloading performance which has an impact on the imbalance between input and output which has an impact on decreasing unloading performance (work performance). Therefore, efforts are needed to increase coal launches, one of which is by optimizing the role of institutions. The purpose of this study was to determine the institutional influence on coal unloading performance. The object of research and the place of its implementation is Tanjung Intan Port of Cilacap. Data processing used quantitative methods, with a simple random sampling of 80 people. The data instrument is a Likert Scale model, the analysis technique uses correlation, regression, determinants, and t-test. This study states that the relationship between institutional variables and coal unloading performance in a fairly strong category is 0.626. The institution has a positive and significant effect on the performance of coal unloading by 39.2% while the rest is influenced by other factors not examined.